Genotypic diversity among p. Parasitica isolates reveled by its-5.8s rdna nucleotide sequences. - Rosa, Daniel Dias; Machado, Marcos Antonio; Targon, Maria Luisa Penteado Natividade; Furtado, Edson Luiz [UNESP] (My University, 2006)
Phytophthora parasitica is been considered one of the most prevalent citrus soilborn pathogens in Brazil. Fourteen isolates were collected in different region of São Paulo state. Amplification of the ITS region using primers ITS1 and ITS2 produced DNA fragments of 812 to 860 bp, that were compared with other sequences obtained to Gene Bank (NCBI). Neighbor-joining analysis, with 1000 bootstrap revealed an average similarity of 99,3 to 100% between the isolates, and 98,1 to 99,9% between S. Paulo state isolates and P. nicotianae (= Phytophthora parasitica) obtained from the Gene Bank (gi|8927482). The ITS1 was more conserved than to the ITS2. This is a good tool for quick diagnosis of Phytophthora citrus dise-ases.
Diversidade de phytophthora parasitica isolados de citrus usando seqüências de nucleotídeos da região its-5.8s rdna
Keywords: Citrus gummosis; ITS; Phylogenetic; Ribosomal DNA